A new Rhagovelia in the armata group from Colombia (Hemiptera: Heteroptera: Veliidae) - Padilla-Gil, Dora N. (Zootaxa, 2011)
Rhagovelia quilichaensis sp. nov. is described from Santander de Quilichao Municipality, Cauca Department, Colombia, and placed in the armata group. A key to the species of Rhagovelia species in the armata group from Colombia is provided.